Strategi Pengembangan Kawasan Wisata Pantai Ujung Suso Di Kabupaten Luwu Timur - Cristien F, Clara; Aksa, Kamran; Yahya, Ilham (Fakultas Teknik Universitas Bosowa, 2024)
Tourism in Burau District, East Luwu Regency has great potential for development. This is because most of the area is a coastal area and borders directly on Bone Bay. Two beaches in Burau District that are popular with tourists are Lemo Beach and Ujung Suso Beach. Ujung Suso Beach, which has a lot of potential to be managed, currently has not received special attention from the East Luwu Regency government. As a result of the government's lack of attention in the process of managing Ujung Suso Beach, it has a negative impact on its natural conditions, such as severe coastal erosion which causes the distance between the seashore and the road to become closer, and increasing piles of rubbish around the beach in the long term can damage the ecosystem on the beach. The Ujung Suso Beach tourist attraction requires supporting facilities. Therefore, currently a regional tourism management strategy is needed that can improve the quality of facilities and infrastructure, and the natural resources of Ujung Suso Beach. The data collected includes visitor data, tourism potential consisting of physical potential, social culture and previous management methods of Ujung Suso Beach. The results of the SWOT analysis show that the Ujung Suso Beach tourist attraction is at the coordinate point in quadrant II with the strategy used to prioritize, namely the WO strategy, where the strategy used to prioritize is taking advantage of opportunities to overcome weaknesses.